Estrus, ovulation time and pregnancy rate responses to two estrus synchronization programs in beef cattle - Mada, Khumran Armiya'u (2012)
The aim of the study was to compare the estrus response, ovulation time and pregnancy rates of Kedah-Kelantan (KK) and Brangus (BR) cattle in Malaysia to progesterone- (P4) and prostaglandin (PGF₂ᾳ) -based estrus synchronization programs. Forty Kedah- Kelantan (KK) and 30 Brangus (BR) cows, were selected and randomly divided equally into two groups per breed. Cows in KK1 and BR1 groups received 2 ml intramuscular (i.m) injection of estradiol benzoate (Cidirol®, 1 mg/ml) at the time CIDR® was inserted into the vagina (Day 0), i.m injection of 1 ml cloprostenol (250μg/ml) at the time of CIDR® removal (Day 9) and 1 ml injection of Cidirol® (Day 10). On the other hand, cows in groups KK2 and BR2 were given PGF₂ᾳ -based treatment. Intramuscular injection of 2 ml (Day 0) and 1ml (Day 11) of Estrumate® (250 μg/ml of cloprostenol), 11 days apart in each cow. All cows were observed for estrus signs and their ovaries scanned for ovulation, followed by AI upon detection of estrus. Pregnancy status was diagnosed 45 days after AI. The present study showed that both treatments (P4- and PGF₂ᾳ-based) were effective in inducing observable estrus signs in all groups with synchrony of ovulation resulting in corpus luteum (CL) development and successful pregnancy in all groups. In the CIDR group, 84.2% and 78.8% of KK and BR cows respectively responded to the treatment. In the PGF₂ᾳ-based protocol, 80.0% of KK exhibited estrus compared with 50.0% BR cows that showed estrus. There were no significant differences in rate of ovulation and pregnancy among the four experimental groups (P > 0.05). However, KK had the higher rate of ovulation over BR: 84.2 vs. 64.3% and 70.0 vs. 42.9% in CIDR and PGF₂ᾳ treatments respectively. The same also holds for the pregnancy rate in KK cows, which produced the higher rate than BR, 31.6 vs. 14.3% for CIDR, and 45.0 vs. 21.4% for PGF₂ᾳ, respectively. The interval from the last treatment to ovulation time varied significantly in these experiments across all groups. The highest median time to ovulation was achieved by BR cows treated with PGF₂ᾳ (84h) and the same BR cows also ovulated the earliest (48h) when treated with CIDR. These variations could be explained by the difference in ovarian status at the time of treatment. In conclusion, the results of this study showed no significant difference between the use of CIDR and PGF₂ᾳ to induce synchronization of estrus in both KK and BR.